2006
DOI: 10.1111/j.1747-0285.2006.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Trypanocidal Compounds by Whole Cell HTS of Trypanosoma brucei

Abstract: Chemotherapy against human African trypanosomiasis relies on four drugs that cause frequent and occasionally severe side-effects. Because human African trypanosomiasis is a disease of poor people in Africa, the traditional market-driven pathways to drug development are not available. One potentially rapid and cost-effective approach to identifying and developing new trypanocidal drugs would be high throughput-screening of existing drugs already approved for other uses, as well as clinical candidates in late de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
99
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 25 publications
4
99
0
2
Order By: Relevance
“…For example, an ATP detection assay that has been used in a 96-well format by Mackey and others, 6 when converted to a 384-well format and assuming a volume of 25 μL/well as suggested by the manufacturer, would result in a reagent cost per well 3.8× greater than that given in this report. Although the HTS Alamar Blue assay we report has a total incubation time of 96 hours, batches of plates could potentially be run in relatively large numbers, which is based on a standard incubator capacity that would be approximately 80-100 × 384-well plates in a 5-day cycle.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…For example, an ATP detection assay that has been used in a 96-well format by Mackey and others, 6 when converted to a 384-well format and assuming a volume of 25 μL/well as suggested by the manufacturer, would result in a reagent cost per well 3.8× greater than that given in this report. Although the HTS Alamar Blue assay we report has a total incubation time of 96 hours, batches of plates could potentially be run in relatively large numbers, which is based on a standard incubator capacity that would be approximately 80-100 × 384-well plates in a 5-day cycle.…”
mentioning
confidence: 49%
“…A luciferase viability assay adapted to a 96-well format has most recently been used for HTS of a small compound library against Trypanosoma brucei brucei . 6 However, this 96-well method is not suitable for undertaking HTS of larger libraries because of the intensive labor requirements and expense. HTS of known HAT targets, such as trypanothione reductase 7 in a 384-well format are documented, but there are no reports of 384-well assays against the whole parasite.…”
Section: Introductionmentioning
confidence: 99%
“…In a second approach, a luciferase-based viability assay was used. T. brucei and HeLa cells (31) were incubated with the compounds for 72 h, and the cellular ATP level was measured (37). The antitrypanosomal effect of the compounds became apparent after 24 h and remained practically constant for 72 h. The mammalian HeLa cells revealed generally higher EC 50 values, which resulted in selectivity indices of up to Ͼ83 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Cell-based phenotypic screening has been useful in identifying new chemotypes against pathogenic protozoa (7,8,11,28). Sharlow et al reported the screening of 196,146 publicly available compounds for activity against Leishmania major promastigotes and identified 17,629 compounds as primary hits (27).…”
mentioning
confidence: 99%